2009
DOI: 10.1089/dna.2009.0930
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Potential of Protoberberine Alkaloids: Spectroscopic and Calorimetric Studies on the Binding of Berberine, Palmatine, and Coralyne to Protonated RNA Structures

Abstract: Interaction of the protoberberine alkaloids berberine, palmatine, and coralyne with the two double-stranded RNA homopolymers of cytidine-guanosine (CG) and inosine-cytidine (IC) sequences in the protonated conformation was investigated using various biophysical techniques. All the three alkaloids bound polyC(+)G in a cooperative way. The binding of coralyne to both the polyribonucleotides was stronger than that of berberine and palmatine. Evidence for the intercalative binding of coralyne was revealed from flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Similar binding constants were estimated for other alkaloids-RNA complexes (Maidul Islam and Kumar, 2009). …”
Section: Stability Of Alkaloid-rna Complexessupporting
confidence: 75%
“…Similar binding constants were estimated for other alkaloids-RNA complexes (Maidul Islam and Kumar, 2009). …”
Section: Stability Of Alkaloid-rna Complexessupporting
confidence: 75%
“…To elucidate this problem further, the binding reactions between RNA and flavonoids in an aqueous phase were studied using ITC. ITC is an important tool for measuring the thermodynamics of interactions between small molecules and biopolymers, in which all binding parameters (n, K, ΔH and ΔS) are simultaneously determined in a single ITC experiment, thus obtaining information that cannot be obtained by other methods [35][37]. In our research, analysis of the ITC measurements revealed two interactions to be primarily enthalpy driven.…”
Section: Discussionmentioning
confidence: 68%
“…Understanding the mechanism(s) of action of berberine is of significant interest and requires further studies. Berberine is a known DNA and RNA binder [45], [11], [46], [47], and recently it was reported to target the bacterial division protein FtsZ [2]. The evidence supporting these findings was obtained mainly through biochemical and biophysical studies.…”
Section: Discussionmentioning
confidence: 96%